Structures, Deformation Mechanisms and Tectonic Phases, Recorded in Paleoproterozoic Granitoids of West African Craton, Southern Part: Example of Kan’s Complex (Central of Côte d’Ivoire) - Pria, K. K. Jean Marie; Coulibaly, Yacouba; Houssou, N. N’guessan; Allialy, M. Ephrem; Boya, T. K. L. Dimitri; Tayebi, Mohamed; Erraoui, Lamia; M’Rabet, Souad (European Scientific Journal, ESJ, 2019)
The granito-gneissic complex of Kan is located in the central part of the Paleoproterozoic domain of CÃ´te dâ€™Ivoire. It consists essentially of migmatitic and mylonitic gneisses with basic intrusions and xenoliths. This Proterozoic domain belongs to the Man Leo shield, southern part of West African craton (WAC). The present study, essentially based on a structural analysis at outcrop scale, aims to identify deformation mechanisms and tectonic phasesrecorded in the granito-gneissic complex of Kan. Deformation mechanisms include: (1) flattening, (2) constriction, (3) simple shear (4), rotation (5), brittle shear, and (6) extension. The Kan complex deformation occurred during four major tectonic phases named D1, D2, D3 and D4. D1 corresponds to WNW-ESE compression. It led to the formation of NS to NNE-SSW foliation, of stretching lineation, and of folds with sub-horizontal axes. It is accompanied by N170Â° and N10Â° sinistral shear zones, which constitute globally a NS major transcurrent shear zone in the central part of CÃ´te dâ€™Ivoire. D1 is also marked by N90Â° dextral shear zones. Tectonic phase D2 is associated with EW compression. It is marked by N50Â° dextral and N110Â° sinistral transcurents shear zones. D3 corresponds to NNE-SSW compressive phase and is responsible of N110Â° crenulation cleavage formation. (D4) constitutes a brittle deformation phase. It correspondsto posteburnean deformation in the Proterozoic crust of CÃ´te d’Ivoire. Generally, these deformation phases are similar to D2 and D3 reported in the Man-Leo shield and that are part of regional collisional phase referred to as Eburnean orogeny in the WAC.